2013
DOI: 10.1111/bjd.12322
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic plaque psoriasis triggered by microbiota in the skin?

Abstract: There is a known association between psoriasis and Crohn disease (CD). Patients with CD are five times more likely to develop psoriasis, and, conversely, patients with psoriasis are more likely to develop CD. Many gastroenterologists now accept that CD results from a breakdown of immune tolerance to the microbiota of the intestine in genetically susceptible individuals. The microbiota of the skin have recently been investigated in psoriasis. Firmicutes was the most common phylum, and Streptococcus the most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 55 publications
0
86
0
5
Order By: Relevance
“…It has been proposed that a maladaptive innate immune response to the skin microbiota may be a key initiating event [5]. Increased numbers of dermal dendritic cells are activated by various innate immune cells, including macrophages, keratinocytes and NK T cells.…”
mentioning
confidence: 99%
“…It has been proposed that a maladaptive innate immune response to the skin microbiota may be a key initiating event [5]. Increased numbers of dermal dendritic cells are activated by various innate immune cells, including macrophages, keratinocytes and NK T cells.…”
mentioning
confidence: 99%
“…While these studies have identified potential differences in the composition of the microbiota between psoriatic and normal skin, no consensus microorganisms have been directly identified and linked to disease pathogenesis. Additionally, the number of innate immune-related genetic factors identified in patients with psoriasis further complicates the issue, again leaving researchers without a definitive cause-and-effect relationship between disease and microbial diversity [79,82]. …”
Section: Consequences Of Dysbiosis In the Microbiomementioning
confidence: 99%
“…Conversely, shifting of microbial communities can alter host–microbiome interactions has been associated with disease [2224]. To better understand those changes in microbial compositions, the dynamics of microbial interactions at the skin surface will be discussed briefly.…”
Section: Host Interactions With Skin Microbiotamentioning
confidence: 99%